Localizing Islamic Economics: Integrating Sharia Principles into the Salingka Nagari Tradition in Minangkabau - Yafiz, Muhammad; Tarigan, Azhari Akmal; Saharuddin, Desmadi; Ismail, Ismail (SCAD Independent, 2025)
This article explored the integration of Islamic economics into the economic life of the Minangkabau people, examined through historical and contemporary perspectives. Using a qualitative approach based on literature study and in-depth interviews, the research investigated how Islamic principles—such as justice, distributive equity, and sharia-compliant resource management—are embedded within Minangkabau socio-economic traditions. Historically, since the era of the Minangkabau Sultanate, Islamic values were institutionalized through customary systems and cooperation mechanisms that regulated economic relations and social solidarity. In the modern context, the dynamics of globalization have introduced Islamic financial institutions, sharia-based enterprises, and structured zakat and waqf management, which coexist with enduring indigenous practices. The findings indicated that despite challenges from conventional economic systems, the synergy between Islamic values and local traditions continues to support community empowerment, inclusive finance, and cultural resilience. This study contributed to Islamic institutional economics and indigenous economic thought by identifying three dimensions of integration: normative, institutional, and practical. These dimensions produce a hybrid model that is adaptive, resilient, and sustainable. Beyond its local relevance, the Minangkabau experience offers insights for Muslim societies worldwide, demonstrating how cultural authenticity and Islamic ethics can be harmonized with modern development to address global economic challenges.